Type IV Coupling Proteins as Potential Targets to Control the Dissemination of Antibiotic Resistance - Álvarez-Rodríguez, Itxaso; Arana, Lide; Ugarte-Uribe, Begoña; Gómez-Rubio, Elena; Martín-Santamaría, Sonsoles; Garbisu, Carlos; Alkorta, Itziar (Frontiers in Molecular Biosciences, 2020)
The increase of infections caused by multidrug-resistant bacteria, together with the loss of effectiveness of currently available antibiotics, represents one of the most serious threats to public health worldwide. The loss of human lives and the economic costs associated to the problem of the dissemination of antibiotic resistance require immediate action. Bacteria, known by their great genetic plasticity, are capable not only of mutating their genes to adapt to disturbances and environmental changes but also of acquiring new genes that allow them to survive in hostile environments, such as in the presence of antibiotics. One of the major mechanisms responsible for the horizontal acquisition of new genes (e.g., antibiotic resistance genes) is bacterial conjugation, a process mediated by mobile genetic elements such as conjugative plasmids and integrative conjugative elements. Conjugative plasmids harbouring antibiotic resistance genes can be transferred from a donor to a recipient bacterium in a process that requires physical contact. After conjugation, the recipient bacterium not only harbours the antibiotic resistance genes but it can also transfer the acquired plasmid to other bacteria, thus contributing to the spread of antibiotic resistance. Conjugative plasmids have genes that encode all the proteins necessary for the conjugation to take place, such as the type IV coupling proteins (T4CPs) present in all conjugative plasmids. Type VI coupling proteins constitute a heterogeneous family of hexameric ATPases that use energy from the ATP hydrolysis for plasmid transfer. Taking into account their essential role in bacterial conjugation, T4CPs are attractive targets for the inhibition of bacterial conjugation and, concomitantly, the limitation of antibiotic resistance dissemination. This review aims to compile present knowledge on T4CPs as a starting point for delving into their molecular structure and functioning in future studies. Likewise, the scientific literature on bacterial conjugation inhibitors has been reviewed here, in an attempt to elucidate the possibility of designing T4CP-inhibitors as a potential solution to the dissemination of multidrug-resistant bacteria.